Evaluation of the in vivo mutagenic potential of hydroalcoholic extracts of the northern highbush blueberry (Vaccinium corymbosum L. Ericales, Ericaceae) on peripheral blood cells of Swiss mice (Mus musculus Rodentia, Muridae) - Freitas, Patrícia Scotini; Andrade, Sérgio Faloni de; Maistro, Edson Luis [UNESP] (Sociedade Brasileira de Genética, 2008)
The northern highbush blueberry (Vaccinium corymbosum L. Ericales, Ericaceae) is very rich in anthocyanins, natural pigments which have strong antioxidant properties and potential health benefits, resulting in the worldwide use the blueberry as a medicinal plant. We investigated the mutagenic potential of simple hydroalcoholic extracts of V. corymbosum acutely administrated by gavage to Swiss mice at doses of 1 g kg-1, 1.5 g kg-1 and 2 g kg-1. Peripheral blood cells were collected 4 h and 24 h post-gavage and assessed by the alkaline comet assay, with further blood samples being collected at 48 h and 72 h for assessment using the micronucleus (MN) assay. Our results show that the V. corymbosum extracts did not induce any statistically significant increase in the average amount of DNA damage in peripheral blood leukocytes. However, we did record a significant increase in the frequency of micronucleated polychromatic erythrocytes at the three doses tested.
Keywords: comet assay; micronucleus; mutagenicity; Vaccinium corymbosum